Academic training of nursing professionals and its relevance to the workplace - Maria del Carmen Barbera Ortega; Diana Cecagno; Ana Myriam Seva Llor; Hedi Crecencia Heckler de Siqueira; Maria José López Montesinos; Loreto Maciá Soler (Universidade de São Paulo, 2015)
OBJECTIVE: to identify the training nursing professionals receive and its relevance to the workplace, as well as professional demand for continuous education.METHODOLOGY: this was a descriptive observational study using a questionnaire entitled "Training and Adaptation of the Nursing Professional to the Workplace" available at: http://enfermeriadocente.es for nursing professionals.RESULTS: 53.8% of nurses do not consider the training received to be relevant to the needs of the workplace and 94.2% reported that linking academic education to the workplace impacts on the quality of care provided.CONCLUSIONS: Nursing professionals think that continuous education needs to be adjusted to their jobs and careers. Education should be viewed as a continuum, which begins with training.